Olivine slurry replenishment and the development of igneous layering in a Franklin sill, Victoria Island, Arctic Canada - Hayes, Ben; Bédard, Jean H.; Lissenberg, C. Johan (Journal of Petrology, 2015)
The Franklin sills and dykes on Victoria Island in the Canadian Arctic represent the sub-volcanic plumbing system to the Natkusiak flood basalts, which are associated with the late Neoproterozoic (c. 723–716 Ma) break-up of Rodinia. The Lower Pyramid Sill (LPS) is the distal end of a sill complex that may be rooted in the Uhuk Massif, a major fault-guided magmatic feeder system. The LPS is unusual for a thin (c. 21 m), shallow, tholeiitic intrusion because it displays well-developed cumulate layering similar to that seen in large layered intrusions. The LPS has an aphanitic, olivine-phyric (c. 5%) Lower Chilled Margin (LCM), a (<1 m thick) dendritic, olivine-phyric Lower Border Zone (LBZ), a (c. 7 m thick) olivine-dominated (up to c. 55%) melagabbro–feldspathic-peridotite zone (OZ), a thin (c. 1 m) clinopyroxene-rich cumulate gabbro (CPZ) containing sector-zoned euhedral clinopyroxene, a (c. 10 m thick) doleritic gabbro zone (DZ), a (<1 m thick) aphyric, dendritic Upper Border Zone (UBZ) and an aphanitic, olivine-phyric (c. 5%) Upper Chilled Margin (UCM). Distinct compositional groups recognized in olivines from the OZ can be associated with specific crystal morphologies, some showing significant reverse zoning. Melt compositions were calculated through application of the olivine–melt Fe ¼ Mg exchange coefficient. The calculations suggest that phenocrystic and primocrystic olivine (Fo88–82) in the LCM–LBZ and lower OZ formed from melts with c. 13–10 wt % MgO. Modeling implies that reversely zoned olivine primocrysts and chadacrysts have rims in equilibrium with melts of c. 10–8 wt % MgO that were saturated only in olivine (þ minor chromite), whereas some olivine cores formed from melts as evolved as c. 6–5 wt % MgO that would have coexisted with a gabbroic assemblage. The presence of multiple olivine populations in the OZ (some reverse zoned) indicates that the LPS did not crystallize from a single pulse of melt that evolved by closed-system fractional crystallization. We propose that the reverse zoning ...